2020
DOI: 10.3390/su12072757
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Sustainability in the Romanian Top Universities’ Strategic Plans

Abstract: The concept of sustainability has been given more and more attention lately as the effects of climate change drastically impact society and threaten the wellbeing of future generations. In this context, universities are expected to build bridges between the academic and research communities on the one hand and society on the other, and to further the values associated with this concept in order to care for the generations to come. Thus, the present study describes the causes that have led to the emergence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…This conclusion is supported also by other scholars [26,27,50], who additionally consider that the concept of sustainability should be explicitly employed in all the policy documents of the university in order to ensure the acquisition of the concept. Hence, the justification of the quantitative and qualitative linguistic analysis performed on the strategic plans for 2016-2020 of the Romanian top universities [50], which has aimed to identify the explicit use of the concept of sustainability, i.e., all its linguistic embodiments: sustainability, sustainable development (durable development) and sustainable, in order to infer the stance taken by these universities towards sustainability by describing the linguistic context in which they appear and by identifying the domains in which a sustainable university should perform [24], namely, (I) quality teaching, (II) research culture, (III) technological capacity building, (IV) accessibility to university education, (V) community engagement, (VI) internationalization and (VII) natural environment. One of the major concerns revealed by the analysis has referred to the availability of financial resources that may be used to find and implement customed sustainable solutions [50].…”
Section: Introductionsupporting
confidence: 58%
“…This conclusion is supported also by other scholars [26,27,50], who additionally consider that the concept of sustainability should be explicitly employed in all the policy documents of the university in order to ensure the acquisition of the concept. Hence, the justification of the quantitative and qualitative linguistic analysis performed on the strategic plans for 2016-2020 of the Romanian top universities [50], which has aimed to identify the explicit use of the concept of sustainability, i.e., all its linguistic embodiments: sustainability, sustainable development (durable development) and sustainable, in order to infer the stance taken by these universities towards sustainability by describing the linguistic context in which they appear and by identifying the domains in which a sustainable university should perform [24], namely, (I) quality teaching, (II) research culture, (III) technological capacity building, (IV) accessibility to university education, (V) community engagement, (VI) internationalization and (VII) natural environment. One of the major concerns revealed by the analysis has referred to the availability of financial resources that may be used to find and implement customed sustainable solutions [50].…”
Section: Introductionsupporting
confidence: 58%
“…Although there have been numerous studies conducted on various topics related to the polytechnic university environment in Timis , oara, such as migration, student values, the development of the concept of sustainability in the University's strategic plan, the use of educational resources, Artificial Intelligence [AI], etc. [18,[38][39][40], none have addressed the issue of online education, either from the perspective of the students or from that of the teachers. Nevertheless, as there are no studies to be found on the perspective of students' online behaviour regarding choosing not to turn on their webcams, as well as on the usage of webcams and their effect on students' behaviour and impact, the present research aims, on the one hand, to identify the motives that the students at the Politehnica University of Timis , oara have regarding the use of webcams in online classes, whatever their behaviour and, on the other hand, to find solutions to improve the online educational process.…”
Section: Contextual Behaviour Of Webcam Users In the Education Online Environmentmentioning
confidence: 99%
“…Even more, environmental sustainability has become a priority for many tertiary institutions and different initiatives have been formulated through declarations to foster sustainable development guidelines on how to incorporate sustainability into the university system [18,70].…”
Section: Paper and Plastic Usementioning
confidence: 99%
“…Prior to the COVID-19 pandemic outbreak in 2020, an event that confined to their homes more than 1.37 billion students of all levels of education, according to the statistics provided by UNESCO [9], studies on students' environment-related behaviors dealt with either their behavior on campus [10], at college or as part of their generation, in the household, from multiple angles-as part of a lifestyle [11], as a consciously adopted choice [12], as perceptions related to sustainability actions in green universities [10], up to behaviors and attitudes on campus [13,14]. Universities also attracted their share of attention, mainly in the form of calls to action under the framework of the United Nations Environment Programme for going green and joining the Green Universities Network (UNEP) [15], or as practices developed on regional or local levels [10,[16][17][18]. The health crisis interrupted much of the habitual academic life and forced universities to focus on their capacity to deliver education and reduce the disruptive force of the pandemic on academic life, by accelerating the adoption of digitalization [19], a topic that was viewed mainly from a technological angle and with an impact on educational practice, but that has a spillover effect on the environmental concerns and greening, if the reduction of physical paper is taken under consideration.…”
Section: Introductionmentioning
confidence: 99%